2012
DOI: 10.1091/mbc.e11-09-0784
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression ofMECP2affects cell commitment and maintenance in neurons by triggering senescence: new perspective for Rett syndrome

Abstract: The neural differentiation process is studied in mesenchymal stem cells obtained from Rett patients and in neuroblastoma cells carrying a partially silenced MECP2 gene. The data suggest that neural cell fate and neuronal maintenance might be perturbed by senescence triggered by impaired MECP2 protein activity either before or after neural differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…Previous research studies on MeCP2 have shown that both deficiency (Nagarajan et al 2006;Squillaro et al 2012;Smrt et al 2007) and overexpression (Bodda et al 2013;Na et al 2012;Collins et al 2004) of MeCP2 lead to severe neurological complications. However, expression and function of MeCP2 in neurodevelopmental disorders are the focus of most MeCP2-related research work.…”
Section: Regulatory Mechanisms Of Mecp2 In Brainmentioning
confidence: 99%
“…Previous research studies on MeCP2 have shown that both deficiency (Nagarajan et al 2006;Squillaro et al 2012;Smrt et al 2007) and overexpression (Bodda et al 2013;Na et al 2012;Collins et al 2004) of MeCP2 lead to severe neurological complications. However, expression and function of MeCP2 in neurodevelopmental disorders are the focus of most MeCP2-related research work.…”
Section: Regulatory Mechanisms Of Mecp2 In Brainmentioning
confidence: 99%
“…In addition to stress-induced senescence, there is also evidence for CS in neuroblastoma cells as a result of altered gene expression. Knockdown of MECP2, a chromatin-modifying protein that mediates gene silencing increases β-gal staining in a neuroblastoma cell line (Squillaro et al, 2012). In neurons, MECP2 mediates the expression of immediate early gene expression, a set of genes important for synaptic plasticity and memory formation (Deng et al, 2014).…”
Section: Senescence In the Cnsmentioning
confidence: 99%
“…This approach allows more accessible cell types, such as dermal fibroblasts from a skin biopsy or lymphocytes in peripheral blood, to be reprogrammed to pluripotent cells. Using this technique, which relies on the expression of cocktails of transcription factors, such as OCT4, SOX2, KLF4 , and c-MYC (10, 12), or OCT4, SOX2, NANOG , and LIN28 (11), there now exist a growing number of human iPSCs models of monogenic psychiatric disorders such as Fragile X syndrome (1315), Rett syndrome (1622), along with smaller number of examples of complex, polygenic psychiatric disorders, including schizophrenia (2326), and bipolar disorder (27). …”
Section: Introductionmentioning
confidence: 99%